2015
DOI: 10.1002/anie.201506545
|View full text |Cite
|
Sign up to set email alerts
|

Classical Amphiphilic Behavior of Nonclassical Amphiphiles: A Comparison of Metallacarborane Self‐Assembly with SDS Micellization

Abstract: The self-assembly of metallacarboranes, a peculiar family of compounds exhibiting surface activity and resembling molecular-scale Pickering stabilizers, has been investigated by comparison to the micellization of sodium dodecylsulfate (SDS). These studies have shown that molecules without classical amphiphilic topology but with an inherent amphiphilic nature can behave similarly to classical surfactants. As shown by NMR techniques, the self-assembly of both metallacarboranes and SDS obey a closed association m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
144
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 64 publications
(148 citation statements)
references
References 46 publications
4
144
0
Order By: Relevance
“…[28] Our very recent contribution to this controversy aimed at rationalizing the solution behavior of metallacarboranes. [27] We demonstrated that COSAN aggregation obeys the rules established for classical surfactants like SDS (the closed association model with critical aggregation concentration (CAC)) pointing to the hydrophobic effect as a general driving force for the selfassembly of all surfactants and amphiphiles. The most important results are briefly outlined: The aggregates (micelles) were visualized by electron microscopy as dark round stains with average diameter 2.59 ± 1.34 nm in 24.5 mm COSAN solution.…”
Section: Introductionmentioning
confidence: 75%
See 4 more Smart Citations
“…[28] Our very recent contribution to this controversy aimed at rationalizing the solution behavior of metallacarboranes. [27] We demonstrated that COSAN aggregation obeys the rules established for classical surfactants like SDS (the closed association model with critical aggregation concentration (CAC)) pointing to the hydrophobic effect as a general driving force for the selfassembly of all surfactants and amphiphiles. The most important results are briefly outlined: The aggregates (micelles) were visualized by electron microscopy as dark round stains with average diameter 2.59 ± 1.34 nm in 24.5 mm COSAN solution.…”
Section: Introductionmentioning
confidence: 75%
“…As a consequence, metallacarboranes aggregate in water. [26,27] Even though metallacarboranes are considered rather exotic compounds, the observed morphologies of the aggregates (large vesicles, layered and cylindrical structures, and small spherical associates) [26][27][28] have their parallels in the field of classical surfactants. Unfortunately, the theories on metallacarborane aggregation usually suffer from the tendencies to exclude boron cluster compounds from classical amphiphiles.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations